Effect of acute exercise on prostate cancer cell growth. - Helene Rundqvist (Public Library of Science (PLoS), 2013)
Physical activity is associated with reduced risk of several cancers, including aggressive prostate cancer. The mechanisms mediating the effects are not yet understood; among the candidates are modifications of endogenous hormone levels. Long-term exercise is known to reduce serum levels of growth stimulating hormones. In contrast, the endocrine effects of acute endurance exercise include increased levels of mitogenic factors such as GH and IGF-1. It can be speculated that the elevation of serum growth factors may be detrimental to prostate cancer progression into malignancy. The incentive of the current study is to evaluate the effect of acute exercise serum on prostate cancer cell growth. We designed an exercise intervention where 10 male individuals performed 60 minutes of bicycle exercise at increasing intensity. Serum samples were obtained before (rest serum) and after completed exercise (exercise serum). The established prostate cancer cell line LNCaP was exposed to exercise or rest serum. Exercise serum from 9 out of 10 individuals had a growth inhibitory effect on LNCaP cells. Incubation with pooled exercise serum resulted in a 31% inhibition of LNCaP growth and pre-incubation before subcutaneous injection into SCID mice caused a delay in tumor formation. Serum analyses indicated two possible candidates for the effect; increased levels of IGFBP-1 and reduced levels of EGF. In conclusion, despite the fear of possible detrimental effects of acute exercise serum on tumor cell growth, we show that even the short-term effects seem to add to the overall beneficial influence of exercise on neoplasia.